Systemic Amyloidosis in England: an epidemiological study. (11th March 2013) - Pinney, Jennifer H.; Smith, Colette J.; Taube, Jessi B.; Lachmann, Helen J.; Venner, Christopher P.; Gibbs, Simon D. J.; Dungu, Jason; Banyperasad, Sanjay M.; Wechalekar, Ashutosh D.; Whelan, Carol J.; Hawkins, Philip N.; Gillmore, Julian D.
Summary Epidemiological studies of systemic amyloidosis are scarce and the burden of disease in England has not previously been estimated. In 1999, the National Health Service commissioned the National Amyloidosis Centre (NAC) to provide a national clinical service for all patients with amyloidosis. Data for all individuals referred to the NAC is held on a comprehensive central database, and these were compared with English death certificate data for amyloidosis from 2000 to 2008, obtained from the Office of National Statistics. Amyloidosis was stated on death certificates of 2543 individuals, representing 0·58/1000 recorded deaths. During the same period, 1143 amyloidosis patients followed at the NAC died, 903 (79%) of whom had amyloidosis recorded on their death certificates. The estimated minimum incidence of systemic amyloidosis in the English population in 2008, based on new referrals to the NAC, was 0·4/100 000 population. The incidence peaked at age 60–79 years. Systemic AL amyloidosis was the most common type with an estimated minimum incidence of 0·3/100 000 population. Although there are various limitations to this study, the available data suggest the incidence of systemic amyloidosis in England exceeds 0·8/100 000 of the population.